الإدارة العصرية للأصول الذكية في ظل اقتصاد المعرفة - محمد، سحنوني Muhammad, Sahnouni (جامعة حسيبة بن بو علي بالشلف - مخبر العولمة واقتصاديات شمال إفريقيا, 2020)
In the era of creativity, innovation, scientific and technological acceleration, as well as competition and global transformations, institutions have become in a critical position to adapt to the demands of the times. The physical aspect of the institution is not enough to create competitive advantage. The last century, or what is called smart assets, which is the focus of modern knowledge-based economy (knowledge economy), In the context of the dynamic environment, the emergence of digitalization and software, and the pursuit of innovation and innovation by enterprises, we have tried to address the problem of how institutions manage their smart assets in the context of knowledge economies, We also discussed IBM's intelligent asset management philosophy and the national company CONDOR, Our study is aimed at finding the most effective ways to manage it, We deal with knowledge management, competency management, and creative management, and we have reached the conclusion that the center of value creation under the knowledge economy is the effective management of the organization's smart assets.
Keywords: إقتصاديات المعرفة -- منظمات الأعمال -- رأس المال البشري -- التفكير الإبداعي